The Importance of the Concept of Water in Biology Education - ÖZALEMDAR, Lütfiye (Journal of Turkish Science Education, 2019)
The purpose of this study is to disclose the units and topics including the concept of water within 9th, 10th, 11th and 12th grades’ biology textbooks that were chosen by the Ministry of National Education (MoNE) Head Council of Education and Morality (HCEM), and provide an overview of the whole content that mentions the concept of water. This qualitative study employed the document review method. The ratio of the number of units including the concept of water in the reviewed biology textbooks/total number of units-number of topics/total number of topics are, respectively 3/3-9/9 for 9th grade, 2/3-8/11 for 10th grade, 3/3-10/12 for 11th grade and 4/4-8/9 for 12th grade. In general, it has been observed that these units/topics address the structure and characteristics of water; its role on nutrition, respiration, circulation, excretory, reproduction, movement, behaviour, energy flow and metabolic events; its significance on living structure, natural resources, energy resources, living spaces, environmental problems and health; and its relationship with osmotic pressure, enzymes, hormones, professional areas and some structures of living beings. Findings revealed that water has a special place in biology education and biology education is an important tool in conveying the significance of water for the living beings. Further studies may focus on the place of water in teaching various disciplines.